2018
DOI: 10.1039/c8se00274f
|View full text |Cite
|
Sign up to set email alerts
|

Facile conversion of levulinic acid to γ-valerolactone using a high surface area magnetically separable Ni/NiO catalyst

Abstract: A study on the conversion of levulinic acid (LA) to γ-valerolactone (GVL) and methyl levulinate (ML) has been done using a high surface area Ni/NiO catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…These results confirm the formation of IrTCPP complex. The IrTCPP complexes display the absence of a peak in the highly shielded region at –2.74 ppm, which is characteristic of N–H protons of TCPP confirmed that iridium ion is bonded to the nitrogen center of TCPP. Similarly, after the iridium ion incorporation into the calix[4]‐pyrrole cavities (See ESI* Figure S2), the absence of a broad N–H proton peak at 7.1 ppm confirms the coordination of iridium ions through the pyrrole nitrogen of the CP ligand.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…These results confirm the formation of IrTCPP complex. The IrTCPP complexes display the absence of a peak in the highly shielded region at –2.74 ppm, which is characteristic of N–H protons of TCPP confirmed that iridium ion is bonded to the nitrogen center of TCPP. Similarly, after the iridium ion incorporation into the calix[4]‐pyrrole cavities (See ESI* Figure S2), the absence of a broad N–H proton peak at 7.1 ppm confirms the coordination of iridium ions through the pyrrole nitrogen of the CP ligand.…”
Section: Resultsmentioning
confidence: 82%
“…After the stipulated period, the reaction mixture was cooled to 25 ° C, filtered, and washed thoroughly with methanol. The resulting purple crystals were air‐dried and washed with dichloromethane (yield 12 %) , . The Iiridium‐incorporated meso‐tetraphenylporphyrin (IrTPP) complex was prepared by dissolving metal salt (IrCl 3 · XH 2 O; 1 mmol) in 5 mL of dry acetone, followed by introducing the solution containing 1 mmol of TPP in 45 mL of dry acetone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive efforts have been made to convert cellulose into ethanol and other biofuels. A recent report compasses the potential use of Ni‐based catalysts as biomass‐derived biofuel blended with gasoline in the synthesis of γ‐Valerolactone (GVL) from levulinic acid . In the study conducted, an excellent conversion of levulinic acid into γ‐valerolactone is reported under mild conditions.…”
Section: Why Renewable Sourcesmentioning
confidence: 99%
“…The catalyst also has inherent lewis and Bronsted acidity, which promotes hydrogenation. The resulting mesoporous Ni/NiO catalyst is magnetically separable and reusable with 5% loss in the activity and 2% loss in GVL selectivity . All the hydrogenation reactions reported in this study were done by taking Ni/NiO as a catalyst.…”
Section: Why Renewable Sourcesmentioning
confidence: 99%